Técnicas de identificación de lesiones por mordedura y su importancia en el descubrimiento de delitos en la investigación forense. - Cajamarca Naranjo, Anthony Lenin (2025)
This study is based on a literature review of bite injury identification techniques and their importance in the discovery of crimes in forensic investigation. The objective is to describe bite injury identification techniques and their importance in the discovery of crimes in forensic investigation using a literature review. Concerning the methodology, a systematic review was conducted in accordance with the PRISMA guidelines, compiling 20 scientific articles in the field of forensic dentistry extracted from databases such as PubMed, SciELO, Google Scholar, LILACS, and Scielo over the past five years. Regarding the results, the study of bite injury identification techniques is recognized as a valid method of forensic investigation due to the uniqueness of the dental arches; however, it has limitations that affect its effectiveness, so it is not considered a method of first choice. Concluding that although the discovery of crimes through the use of bite injury identification